The relationship between study habits and academic achievement: the case of Ethiopian Adventist College - Gizachew, Mandado (Indonesian Journal of Curriculum and Educational Technology Studies, 2025)
This study explored the relationship between study habits and academic achievement among undergraduate Accounting and Finance students at Ethiopian Adventist College. Employing a descriptive survey design, data was collected from a random sample of 206 first- and second-year students using questionnaires and their first-semester GPA records obtained from the college registrar. Statistical analyses, including Pearson correlation, t-tests, one-way ANOVA, and linear regression, were conducted at a 0.05 significance level. The findings indicated a significant positive correlation between study habits and academic performance. Among the three subcategories of study habits—time management, study attitude, and study methods—time management emerged as the strongest predictor of academic success. Additionally, first-year students outperformed second-year students academically, and significant differences in study habits were observed across students with varying GPA levels. Based on these findings, the study recommends enhancing guidance and counselling services and revisiting evaluation mechanisms to foster effective study habits and improve academic outcomes.